The Sunshine Club [large type] - Brown, Carolyn, 1948- (Center Point Large Print, 2022)
"Gussie, Ina Mae, and Blanche have been best friends for more than sixty years. From their humble beginnings of founding the Sunshine Club when they were girls to becoming the matchmaking queens of Newton, Texas, these three were inseparable. When Blanche passes away, Gussie and Ina Mae feel the best way to honor their dearly departed is with a shot of whiskey, some good music, and making a match for Blanche's niece, Sissy. Never mind that Sissy's in town for only six weeks. Is there a better reason for her to stay? And is there a better prospect than handsome, charming, blue-eyed local preacher Luke Beauchamp? No and no. The attraction is already there. Now it's up to Gussie and Ina Mae to make sure the sparks really get to crackling by Christmas. The Sunshine Club is back in business. Don't underestimate two feisty women who have their hearts set on a happy ending."--